2022
DOI: 10.1080/16066359.2022.2040488
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use disorder relapse factors: an exploratory investigation of craving, alcohol dependence severity, and meaning in life

Abstract: For decades predictors of alcohol use disorder (AUD) relapse have been studied, and around 40 different clinical and demographic relapse determinants have been identified. This paper aims to investigate the relationship of two of these AUD relapse factors, namely craving and meaning in life (MiL). We hypothesized that greater meaning in life would be associated with lower cravings and lower relapse rates. An AUD subsample of 81 patients within a clinical population that participated in ongoing exploratory rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 93 publications
0
5
0
1
Order By: Relevance
“…Future studies could also further explore the idiosyncratic nature of search for meaning in life, such as through the use of qualitative research, to better understand how this construct relates to patterns of alcohol consumption across different people. Interestingly, Sliedrecht et al (2022) prospectively followed up a clinical sample of people in treatment for alcohol use disorder (AUD) and found no significant associations between meaning in life and levels of craving or alcohol relapse. It is important to note that previous research on recovery (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could also further explore the idiosyncratic nature of search for meaning in life, such as through the use of qualitative research, to better understand how this construct relates to patterns of alcohol consumption across different people. Interestingly, Sliedrecht et al (2022) prospectively followed up a clinical sample of people in treatment for alcohol use disorder (AUD) and found no significant associations between meaning in life and levels of craving or alcohol relapse. It is important to note that previous research on recovery (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the research results indicate that people with AUD have a lower sense of meaning of life, and its higher values are a protective factor for alcohol use and abuse [36][37][38]. However, there are also reports that do not indicate any differences in the sense of meaning of life between people with and without AUD [39] and those which do not confirm its protective role for alcohol abuse [40] or the relapse prevention [41,42]. Our research, however, has shown that patients with AUD in an advanced therapy programme achieve lower results than people without AUD in terms of life control (one of the dimensions of the sense of meaning of life).…”
Section: ■ Omówieniementioning
confidence: 95%
“…In particular, the first 3 months of abstinence constitute the period of greatest vulnerability,4 and more than half of patients will consume their first drink (lapse) within 2 weeks 5. Craving is one of the main predictors of relapse6–9 and is triggered by drug use, drug-associated environmental cues and stress 10–12. It is therefore necessary to manage craving, through therapy allowing patients to better handle daily stress and cue exposure.…”
Section: Introductionmentioning
confidence: 99%